Empowering Adolescent Girls in Uganda - Bandiera, Oriana; Buehren, Niklas; Burgess, Robin; Goldstein, Markus; Gulesci, Selim; Rasul, Imran; Sulaiman, Munshi (World Bank, Washington, DC, 2016)
The productive potential of adolescent girls in Uganda is critically limited by the reciprocal relationship between low health, education and employment indicators. With little incentive to attain relevant skills training, girls choose to have children early and become engaged in risky behavior, further hampering their ability to generate income. To address these challenges, we evaluated the impact of a BRAC program that simultaneously provided livelihoods training to run small-scale enterprises, and education on health and risky behaviors. After tracking 4,888 girls over a period of two years, the author found that the program had strong positive impacts on economic, health and agency outcomes for the girls. The program increased the likelihood of participants engaging in income-generating activities by 32 percent; self-reported routine condom use by those who were sexually active increased by 50 percent; fertility rates dropped by 26 percent; and there was a 76 percent reduction in adolescent girls reporting having had sex against their will during the past year.